The degree of expression OF Ki-67 protein and oncoprotein p16INK4A in differential diagnosis of squamous intraepithelial lesions and cancer of cervix uteri - Pliten, Oksana M. (Journal of Education, Health and Sport, 2015)
Pliten O. N. Степень экспрессии белка пролиферации Ki-67 и онкопротеина p16INK4A в дифференциальной диагностике плоскоклеточных интраэпителиальных поражений и рака шейки матки = The degree of expression OF Ki-67 protein and oncoprotein p16INK4A in differential diagnosis of squamous intraepithelial lesions and cancer of cervix uteri. Journal of Education, Health and Sport. 2015;5(7):71-90. ISSN 2391-8306. DOI 10.5281/zenodo.19213 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A71-90 https://pbn.nauka.gov.pl/works/577071 http://dx.doi.org/10.5281/zenodo.19213 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 30.06.2015. СТЕПЕНЬ ЭКСПРЕССИИ БЕЛКА ПРОЛИФЕРАЦИИ KI-67 И ОНКОПРОТЕИНА P16INK4A В ДИФФЕРЕНЦИАЛЬНОЙ ДИАГНОСТИКЕ ПЛОСКОКЛЕТОЧНЫХ ИНТРАЭПИТЕЛИАЛЬНЫХ ПОРАЖЕНИЙ И РАКА ШЕЙКИ МАТКИ THE DEGREE OF EXPRESSION OF KI-67 PROTEIN AND ONCOPROTEIN P16INK4A IN DIFFERENTIAL DIAGNOSIS OF SQUAMOUS INTRAEPITHELIAL LESIONS AND CANCER OF CERVIX UTERI О. Н. Плитень O. N. Pliten Харьковский национальный медицинский университет Kharkiv National Medical University Abstract. This research of expression of proliferation protein Ki-67, index of proliferative potential of the cells, and oncoprotein p16INK4a, index of malignant transformation of the cells, reveals a direct correlation between the indicators of their level of activity and the degree of cellular and tissue atypism of stratified squamous epithelium of the uterine cervix. The revealed indicators can serve as pathomorphological criteria of differential diagnosis of epithelial dysplasia of cervix uteri, intraepithelial carcinoma and invasive cancer. Key words: uterine cervix, squamous intraepithelial neoplasias, cancer, proliferation protein Ki-67, oncoprotein p16INK4a. Резюме. Исследование экспрессии белка пролиферации Ki-67, показателя пролиферативного потенциала клеток, и онкопротеина p16INK4a, маркера злокачественного превращения клеток, выявляет прямую зависимость между показателями их уровня активности и степенью клеточной и тканевой атипии многослойного плоского эпителия шейки матки. Обнаруженные показатели могут служить патоморфологическими критериями в дифференциальной диагностике эпителиальных дисплазий шейки матки, интраэпителиальной карциномы и инвазивного рака. Ключевые слова: шейка матки, плоскоклеточные интраэпителиальные неоплазии, рак, белок пролиферации Ki-67, онкопротеин p16ІNK4a.